Design, control, and development of a low-cost single-tilt-rotor Tricopter - Fahmizal Fahmizal; Ahmad Jaelani Sidik; Priyova Muhammad Rafief; Hari Maghfiroh; Mariusz Jabłoński; Piotr Borkowski (Teknomekanik, 2026)
This paper presents the design, implementation, and experimental validation of a low-cost PID-based attitude control system for a single-tilt-rotor tricopter. The proposed platform employs a Y-shaped frame configuration with a servo-driven tail-tilt mechanism and is implemented using a low-cost ATmega328P microcontroller and GY-88A IMU sensor. A PID controller was used for inner-loop attitude stabilization of roll, pitch, and yaw motions due to its low computational complexity and suitability for resource-constrained embedded systems. The PID gains were obtained through manual tuning using a tricopter test-bed rig under disturbance-free conditions and experimentally evaluated under both static and dynamic wind disturbances. Under a static wind disturbance of 7.2 m/s, the roll and pitch mean absolute error (MAE) values reached 0.977° and 4.826°, respectively, while dynamic disturbance testing produced MAE values of 0.823° for roll and 2.094° for pitch. Outdoor flight tests resulted in MAE values of 1.133° for roll and 1.831° for pitch. The experimental results demonstrated that the proposed low-cost tricopter platform can maintain stable attitude control under the evaluated disturbance conditions and outdoor flight scenarios. The study highlights the feasibility of implementing reliable tricopter stabilization using computationally lightweight PID control on inexpensive embedded hardware.